Bone morphogenetic protein 2 promotes human trophoblast cell invasion and endothelial‐like tube formation through ID1‐mediated upregulation of IGF binding protein‐3. Issue 2 (3rd January 2020) - Zhao, Hong‐Jin; Klausen, Christian; Zhu, Hua; Chang, Hsun‐Ming; Li, Yan; Leung, Peter C. K.
Abstract: Extravillous cytotrophoblasts (EVTs) invade into the uterine wall and remodel spiral arteries for proper placentation. Studies from us and others have demonstrated that the transforming growth factor‐β superfamily member bone morphogenetic protein 2 ( BMP2) plays important roles in endometrial decidualization and trophoblast cell invasion. However, BMP2 has also been shown to regulate endothelial cell migration and capillary‐like tube formation, as has its downstream signaling molecule inhibitor of DNA binding 1 (ID1). Interestingly, insulin‐like growth factor binding protein 3 (IGFBP3) also promotes cell migration and angiogenesis in endothelial precursor cell. Moreover, Id1 has a regulatory effect on Igfbp3 expression in rat prostate epithelial cells. However, whether ID1 and IGFBP3 are integrated in BMP2 signaling and involved in the regulation of trophoblast invasive and endovascular differentiation remains unknown. The objective of our study was to examine the effects of BMP2 on ID1 and IGFBP3 expression and their roles in BMP2‐regulated human trophoblast invasion and endothelial‐like tube formation. Primary and immortalized (HTR8/SVneo) cultures of human trophoblast cells were employed as study models. BMP2 treatment increased ID1 and IGFBP3 mRNA and protein levels in HTR8/SVneo and primary human EVT cells. Intriguingly, ID1 was essential for BMP2‐induced IGFBP3 upregulation in both study models, and BMP2‐induced trophoblast invasion was attenuated by knockdown of either ID1 or IGFBP3. In addition, BMP2 significantly increased endothelial‐like tube formation and knockdown of ID1 and IGFBP3 reduced basal and BMP2‐induced tube formation in HTR8/SVneo cells. Similarly, BMP2 increased placenta growth factor (PlGF) production in HTR8/SVneo cells and these effects were attenuated by knockdown of ID1 or IGFBP3. Our results reveal that BMP2 promotes trophoblast cell invasion and endothelial‐like tube formation by ID1‐mediated IGFBP3 upregulation.